Analisis Faktor Faktor Yang Mempengaruhi Kebijakan Deviden Pada Perusahaan Manufaktur Yang Terdaftar Di BEI 2012-2016 - Ristionom Debataraja; Mintauli Debataraja; Putri Apriliani Jamaludin (IJAcc, 2020)
Dividend are payments made by a corporate to shareholder members which is depend on the dividend policy of each company. The objective of this research is to analyze the influence of cash ratio, debt to equity ratio and return on asset to dividend policy from sample of companies. The population of this research is manufacture companies which listed in Bursa Efek Indonesia (BEI), there is 24 companies. Research sample using purposive sampling of companies for periode ended 2012 – 2016. Analyzed by using the two tail linear regression method. The result show, debt to equity ratio and return on asset had a positive and significant effect to dividend policy. It proved by significant t value lower than 5% significances.